The Anglo-Latin Poetic Tradition: Sources, Transmission, and Reception, ca. 650–1100 - Curran, Colleen M. (Arc Humanities Press, 2024)
This volume presents new perspectives on the sources, transmission, and reception of Anglo-Latin poetry, ca. 650–1100. In the wake of recent seminal studies on Aldhelm, these essays collectively explore the wider poetic tradition, spanning the Late Antique inheritance through to the eleventh century. By encompassing select studies of both major and lesser-known authors, sources, and works, the volume can present new understandings of the multifaceted intellectual culture that gave rise to this unique and vibrant literary period. It engages with the medium of poetry, including manuscript culture, historical and intellectual backgrounds, and the epigraphic traditions; and highlights idiosyncratic style, metre, poetic diction, and formulas. The Anglo-Latin poetic tradition is notoriously and deliberately challenging, but this accessible collection yields rich new insights from emerging and established Anglo-Latin scholars.